Probability applications in mechanical design - Fisher, Franklin E., 1933- (Marcel Dekker, 2000)
This text seeks to clarify mechanical fatigue and design problems by applying probability and computer analysis, and further extending the uses of probability to determine mechanical reliability and achieve optimization. It solves examples using commercially available software.
Keywords: Machine design -- Statistical methods.; Probabilities.; Probability; Machines -- Conception et construction -- Méthodes statistiques.; Probabilités.; probability.; TECHNOLOGY & ENGINEERING -- Machinery.; Machine design -- Statistical methods; Probabilities; Andre fag (naturvidenskab og teknik) -- Andre fag